Irish inflation in EMS - Honohan, Patrick; Flynn, John (Economic & Social Studies, 1986)
This paper outlines the interaction of Irish prices and wages, and highlights the crucial importance of foreign price movements in determining inflation in Ireland. The discussion is based on quarterly empirical estimates for the period 1972-84, covering both the sterling link and EMS regimes. The potential role of exchange rate policy, within the EMS, in influencing inflation is also analysed at a theoretical level.
Keywords: Prices and wages; European Monetary System (EMS)